Pertumbuhan dan Hasil Tanaman Tomat Hitam Indigo Rose (Lycopersicum Esculentum Var. Indigo Rose) pada Dua Ketinggian Tempat Berbeda - Pratiwi, Diajeng; Syarif, Zulfadly; Irawati, Irawati (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
This study aims to determine the differences in growth and yield of Indigo Rose black tomato plants at two different altitudes. The research was conducted in October 2018 until January 2019 in two different locations. The first location in Bulakan Balai Kandi Village, West Payakumbuh, Payakumbuh City with an altitude of 500 m above sea level (asl) and the second location in Jorong Koto Laweh Puncak Alai, Tanjung Alam Subdistrict Tanjung Baru, Tanah Datar Regency with an altitude of 1300 m asl. This study used the experimental method in two different locations, quantitative data obtained from the observations were analyzed by independent t test at the level of 5%. The parameters observed were plant height, age of first flower appearance, number of productive branches, stem diameter, age of first harvest, number of fruits per plant, fruit diameter and weight of fruit per plant. The results showed that there were differences in growth and yield of Indigo Rose black tomato plants at two different altitudes. The best growth and yield of Indigo Rose black tomato plants is grown in the highlands.